2009
DOI: 10.2319/083107-405.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Dental Roots and Surrounding Tissues for Orthodontic Miniscrew Installation

Abstract: Objective: To elucidate relationships between the dental roots and surrounding tissues in order to prevent complications after placement of a miniscrew. Materials and Methods: Twenty human mandibles and maxillas were used for this study. In the 200 sections of each mandible and maxilla, nine items were measured to investigate the relationships between the dental roots. Results: The interroot distance increased from anterior to posterior teeth and from the cervical line to the root apex in both the maxilla and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
38
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 10 publications
10
38
1
5
Order By: Relevance
“…In the posterior region of the maxilla and the mandible the most suitable sites are between the second premolar and the first molar and between the first and second molars, which was also recommended in previous studies. 8,12,18 In the present study, males had a significantly thicker buccolingual dimension and buccal cortical thickness than females in both the maxilla and the mandible. Kim et al 22 found no statistical difference between sexes in the interradicular measurements of the posterior maxilla, probably because of the small sample size (35 patients).…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…In the posterior region of the maxilla and the mandible the most suitable sites are between the second premolar and the first molar and between the first and second molars, which was also recommended in previous studies. 8,12,18 In the present study, males had a significantly thicker buccolingual dimension and buccal cortical thickness than females in both the maxilla and the mandible. Kim et al 22 found no statistical difference between sexes in the interradicular measurements of the posterior maxilla, probably because of the small sample size (35 patients).…”
Section: Discussionsupporting
confidence: 45%
“…The availability of a relatively large number of CBCT images for this study allowed the researchers to overcome the shortcoming of limited sample size in several previous studies. 11,12,18 Most studies on this topic have aimed to determine the safest sites for mini-screw placement by focusing on the posterior region of the jaws. [8][9][10][11] The fact, however, that mini-implants are often useful in the anterior region for space closure 4 or correction of overbite problems 6 necessitated the evaluation of the anterior region as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probable reason for these failures may be the operator's ease (or difficulty) of placement on one side. Schnelle et al 18 and Hu et al 21 advised placement of implants of the smallest diameter and length in these risky areas in order to achieve stability. In this study, if higher force levels were used, the success rate might have been different.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical movement of the center of resistance was 1.9 mm in the implant group and 1.4 mm in the utility arch group. Several studies [21][22][23][24] have found various amounts of lower incisor intrusion (1.02-3 mm) with conventional mechanics. In these studies protrusion of the lower incisors followed intrusion.…”
Section: Discussionmentioning
confidence: 99%